Cross-Floor Vibration Wave Propagation in High-Rise Industrial Buildings Under TMD Control - Ruoyang Zhou; Xiaoxiong Zha (Infrastructures, 2025)
High-rise industrial buildings are particularly susceptible to vibration-induced comfort issues, which can negatively impact both the health and productivity of workers and office staff. Unlike most existing studies that focus on local structural components, this study proposes and validates a wave propagation analysis (WPA) method to predict peak accelerations of the floor caused by excitations located on different floors. The method is validated through on-site vibration tests conducted on a high-rise industrial building with shared factory and office space. A simplified regression-based propagation equation is further developed to facilitate practical design applications. The regression parameters are fitted using theoretical calculation results, enabling rapid prediction of peak acceleration responses on the same or different floors. To enhance vibration control, tuned mass dampers (TMDs) are installed on selected floors, and additional tests are conducted with the TMDs activated. An insertion loss-based correction is introduced into the WPA framework to account for the TMD’s frequency-dependent attenuation effects. The extended method supports both accurate prediction of vibration reduction and optimisation of TMD placement across multiple floors in high-rise industrial buildings.